Guilty by Anticipation: Distortions on the Presumption of Innocence in First Appearance Hearings - Souza, Jaime Luiz Cunha; Silva, José Vicente Braga (Advances in Social Sciences Research Journal, 2023)
This article addresses the dynamics of first appearance hearings and analyzes how the various actors involved in the process influence judges’ decisions. The analysis focuses on the distortion of the presumption of innocence principle based on racial factors, education levels, the criminal record of the arrested person and the type of offense that led to the arrest. Researchers collected data through in-person observations of 63 hearings that took place in the Criminal Court[1] of the city of Belém-Pará-Brazil, from January and March 2020. Results show that the presumption of innocence has little weight in first appearance hearings and factors related to race, education level, criminal background and involvement with drugs often cause the accused to be held in pre-trial detention before being judged and receiving a formal punishment.